2022
DOI: 10.3390/ijms231911172
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Phytochemical Profile of Ocimum basilicum var. minimum (L.) Alef. Essential Oil, Its Larvicidal Activity and In Silico Interaction with Acetylcholinesterase against Aedes aegypti (Diptera: Culicidae)

Abstract: Aedes aegypti L. (Diptera: Culicidae) is an important transmitter of diseases in tropical countries and controlling the larvae of this mosquito helps to reduce cases of diseases such as dengue, zika and chikungunya. Thus, the present study aimed to evaluate the larvicidal potential of the essential oil (EO) of Ocimum basilicum var. minimum (L.) Alef. The EO was extracted by stem distillation and the chemical composition was characterized by gas chromatography coupled with mass spectrometry (GC/MS and GC-FID). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…L has the potential as an Aedes sp larvicide with LC 50 and LC99 of 1040 ppm and 2439 ppm, respectively. Research by Botelho et al 12 also found that Ocimum basilicum var. minimum (L.) Alef.…”
Section: Introductionmentioning
confidence: 90%
“…L has the potential as an Aedes sp larvicide with LC 50 and LC99 of 1040 ppm and 2439 ppm, respectively. Research by Botelho et al 12 also found that Ocimum basilicum var. minimum (L.) Alef.…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, a pertinent investigation revealed that the key components of the essential oil, including limonene, 1,8-cineole, linalool, and methyl chavicol, exhibit larvicidal properties against Ae. aegypti larvae and demonstrated their capacity to interact with AChE (Botelho et al, 2022).…”
Section: The Interactions Between Juvenile Hormones (Chainmentioning
confidence: 99%
“…Aedes aegypti L. is responsible for transmitting arboviruses that cause diseases such as yellow fever, dengue, chikungunya, and zika in tropical regions [13][14][15]. Rapid urbanization, a lack of infrastructure, and poor sanitation are ideal circumstances for the spread of this female Aedes aegypti mosquito, which is resistant to pesticides and commercialized repellents [13,15]. Furthermore, the drawbacks of chemical pesticides, such as pollutants and harm to non-target species, have limited their widespread usage [16].…”
Section: Introductionmentioning
confidence: 99%